Effects of different gluteal strengthening programs on strength, pain, functional disability and balance among university students with nonspecific chronic low back pain: A randomized controlled trial - Lee, Kah Yi (2022)
Background and Objective: Non-specific low back pain (LBP) has become a common health issue encountered by university students nowadays. Gluteal strengthening program was being prescribed for the management of LBP due to the association of glutes and spine. However, there is lack of study conclude that which gluteal strengthening program is more effective to treat LBP among university student. Therefore, the aim of this study was to determine whether the novel gluteal strengthening program (NGSP) has more effects on strength, pain, functional disability and balance compared to the standard gluteal strengthening program (SGSP) among university students with non-specific chronic LBP. Methods: A randomized controlled trial was conducted for 4 weeks and 40 subjects with chronic non-specific LBP are recruited through simple random sampling. Participants were randomly assigned into control group (n=20) and intervention group (n=20). Trunk and gluteal muscle strength, functional disability, pain, and balance was measured at baseline and following 4 weeks of interventions. Trunk and gluteal muscle strength were measured using a hand-held dynamometer, pain intensity assessed by Visual Analogue Scale (VAS), functional disability measured by Oswestry Disability Index (ODI) and the balance was assessed by Y-balance test. The data collected were then analyzed using Paired-samples t-test and independent-samples t-test in IBM SPSS software statistics version 20. Results: A total of 40 participants were recruited but only 36 of them (male = 14, female = 22) with the mean age of 20.94 ± 1.76 completed the study. For strength, pain, functional disability, and balance, there were significant differences between pre- and post-test (p < 0.05). However, there was no difference in all variables measured between both groups (p > 0.05). No sex difference was reported for all variables. Conclusion: NGSP and SGSP are equally effective in improving trunk and gluteal muscle strength, pain, functional disability and balance but NGSP is recommended because it is time-effective, contains a lesser number of exercise and no equipment is required for the exercise when compared to SGSP.